Agrometeorological modeling for coffee productivity forecast in the south region of Minas Gerais state - Victorino, Euler Cipriani; Carvalho, Luiz Gonsaga de; Ferreira, Daniel Furtado (Coffee Science - ISSN 1984-3909, 2016)
Knowledge of effective crop forecasting techniques is of great importance for the coffee market, enabling better planning and making more sustainable this activity. This study aimed to adapt a predictive model of coffee yield, based on water availability, to the cities of Lavras and Varginha, in southern Minas Gerais, Brazil. The models were generated from multiple linear regression of productivity loss (Ye/Yp) as a function of the previous year productivity (Ya/Yp) and water deficit in the different phenological phases, represented by relative evapotranspiration (ETR/ETP)i. During the parameterization, the water deficit response coefficients (Kyi) and the previous year production coefficient (Ky0) were obtained. By the backward selection methodology, were obtained models that presented only significant coefficients. In this process, in general, the models were highly sensitive to the rainy season (November to April), and variables related to important periods such as flowering were not significant. It was concluded that the models have good potential for coffee crop forecasting. In these, previous year’s yield should be considered and the phenological sequence with best performance was Sep./Oct, Nov./Dec., Jan./Feb., Sep. /Apr.